Ceramaster japonicus Sladen 1889 - Mah, Christopher L. (Zenodo, 2016)
Ceramaster japonicus (Sladen, 1889) Sladen 1889: 272; Goto 1914: 313 (as Pentagonaster ) Verrill 1899: 179 (as Mediaster ) Fisher 1911: 206; Djakonov 1950: 46 (1968: 390); Baranova 1957: 161; Imaoka et al. 1990: 48; A.M. Clark 1993: 249; Lambert 2000: 57; Takahashi et al. 1997: 3105 (Table 1); Fujikura et al. 2008: 271 (as Ceramaster japonicus ) Comments. Ceramaster japonicus is present at bathyal depths (194–1437 m) and occurs across a relatively wide range (Northern Japan to Aleutian Islands to Oregon). Although very little is known about the biology of this species, it has been observed in situ by the Japanese submersible Shinkai 2000 in Sagami Bay displaying a large swollen disk. Because sediment is never present in the guts of collected specimens and because the abactinal surface is often distended, it seems most likely that these were filled with seawater (Fujikura et al. 2008). The pollutant butylin has been found from individuals of this species from Suruga Bay, Japan (Takahashi et al. 1997). Occurrence. Tosa Bay, Sagami Bay, Suruga Bay, Sea of Okhotsk, Aleutian Islands, Bering Sea, British Columbia, Washington, Oregon. 194–1490 m Material examined. USNM 38875 Honshu Island, Sagami Bay, 916 to 1370 m. Coll. USFC Albatross 3 wet specs. USNM 32241, Cape Meares, Oregon. 45º30’N, 124º 52’W, 1437 m. Coll. USFC Albatross 3 dry specs R=6.2, r=3.9, R=5.2, r=3.4; R=6.0, r=3.8; CASIZ 106926, Bower’s Bank, Bering Sea. 0º33’N, 178º44’E, 1068 m (584 fms). Coll. USFC Albatross. 1 dry spec. R=6.7, r=5.2 Published as part of Mah, Christopher L., 2016, Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species, pp. 101-141 in Zootaxa 4175 (2) on page 113, DOI:10.11646/zootaxa.4175.2.1, http://zenodo.org/record/257286